2017
DOI: 10.17267/2594-7907ijhe.v1i1.1234
|View full text |Cite
|
Sign up to set email alerts
|

From Intuition to Professionalization: A Qualitative Study About the Development of Teacher Identity in Internal Medicine Senior Residents

Abstract: Objectives: Professional identity can be defined as a developmental process. Literature suggests that residents aiming to practice in a teaching institution should receive support for the development of teaching competencies as much as they do for medical competencies, but there is limited data on how to recognize teacher identity development in residents. Our study focused on the manifestations of teacher identity development in a group of senior residents in a four-week optional pedagogy rotation. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The qualitative results enriched those findings by illustrating how the degree of improved pedagogical practice (‘better’ teaching) was intimately linked to the extent of the evolved posture as clinical teachers (‘better’ attitude). This co-construction of pedagogical competencies and professional identity on the path towards excellence as clinical teachers is congruent with works by Starr et al [ 58 ], Steinert et al [ 76 ] and others [ 59 , 68 ]. As the development of supervision skills improved participants’ practice, their self-confidence in establishing pedagogical diagnoses and issuing pedagogical prescriptions improved.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The qualitative results enriched those findings by illustrating how the degree of improved pedagogical practice (‘better’ teaching) was intimately linked to the extent of the evolved posture as clinical teachers (‘better’ attitude). This co-construction of pedagogical competencies and professional identity on the path towards excellence as clinical teachers is congruent with works by Starr et al [ 58 ], Steinert et al [ 76 ] and others [ 59 , 68 ]. As the development of supervision skills improved participants’ practice, their self-confidence in establishing pedagogical diagnoses and issuing pedagogical prescriptions improved.…”
Section: Discussionsupporting
confidence: 85%
“…This instrument has been used as a self-evaluation instrument (modified MCTQ, mMCTQ) to identify self-perceived training needs in clinical teachers [ 55–57 ]. It aims at evaluating the quality of individual clinical teacher’s supervision through the dimensions of Role modeling , Coaching , Articulation , Exploration , and Learning environment ( Table 1 , dimensions 1–5).Qualitative [ 58 , 59 ] and quantitative [ 60 ] evidence has suggested that excellent clinical teachers have a well-developed teacher identity in addition to their clinician identity. To explore the relationship between clinical reasoning supervision competencies and the development of a clinical teacher professional identity, we added questionnaire items on an additional dimension, Professional identity development ( Table 1 , dimension 6).…”
Section: Methodsmentioning
confidence: 99%
“…An important factor at play with regards to FD generated change at an individual level is related to identity development. Clinical teachers have a dual identity: to provide patient care and to teach 4750…”
Section: The Evolution Of Faculty Development In Medical Educationmentioning
confidence: 99%
“…Supervisors didn't anticipate the cognitive load required to explain their clinical reasoning processes, the supervision plan-ning, and the emotional load not only of having to "share" their patients with a student, but also to take on the responsibility of their emotional reactions (Muller-Juge et al, 2018). It also appeared that these primary care physicians were surprised to find out that it was a challenge to conjugate their two roles: the role of a clinician who takes care of patients, and the role of teacher (Audétat, Grégoire, Fernandez, & Laurin, 2017).…”
Section: Introductionmentioning
confidence: 99%